Potential of eucalyptus plantation in Malaysia - Samdin, Zaiton; Md. Tahir, Paridah; Abdul Hamid, Hazandy; Azim, R. A. R. A. (Forestry Department Peninsular Malaysia, 2018)
Eucalyptus is known as one of the fast growing species and recognised as a potential plantation species. Eucalyptus appear to be a genus with the greatest potential to provide supplemental fiber in many parts of the world. Likewise Eucalyptus species have been planted in several areas in Peninsular Malaysia, Sabah and Sarawak for several decades with mixed results. A study was undertaken to identify the drive, motivation, issues and challenges faced by the Eucalyptus planted in Malaysia. Motivational factors to grow and process Eucalyptus were being perceived as a potentially profitable species. Pulp and paper, sawn timber, laminated timber, woodchip, plywood and veneer were identified as the preferred final products. Planters and industry players had no issues or problems in the supply of Eucalyptus seedlings as almost all of them had their own orchard or nursery. All the industry players are of the opinion that the government should support the establishment of Eucalyptus plantation industry by providing financial assistance and by promoting more research and development activities to ensure the sustainability of the trees, as well as, the wood quality. The study revealed that Eucalyptus planters are not dependent on the local timber market, and that export market offers much greater possibilities. Eucalyptus is expected to progress as an important species in Malaysia with future opportunities for growth.